LC-MS Method for the Detection and Quantification of Ursolic Acid and Uvaol Levels in Olive Leaves and Oregano - Al-Tannak, Naser F.; Novotny, Ladislav (Emirates Journal of Food and Agriculture, 2020)
Ursolic acid and uvaol belong to pentacyclic triterpenes are both secondary metabolites with significant biological activity. Ursolic acid and uvaol are exist in many natural matrices such as olive leaves, oregano and thymus. Therefore, a new rapid and validated UPLC method was developed to identify and quantify ursolic acid and uvaol in dry olive leaves (Olea europaea L.) planted in Kuwait and dry oregano (Origanum vulgare L.) planted in Palestine and Spain. The separation of ursolic acid and uvaol was achieved by using BEH Phenyl (1.7 μm, 2.1 x 100 mm) analytical column (Waters® Acquity UPLC) and a mobile phase composed of water and acetonitrile (37:63 v/v). Solid-phase extraction cartridges (HyperSep™) was used to extract ursolic acid and uvaol from natural matrices. Ursolic acid and uvaol were detected in all-natural matrices used. The concentrations of ursolic acid and uvaol in olive leaves were 55.10 μg/g ± 0.72 and 314.29 μg/g ± 0.97, respectively. In contrast, ursolic acid and uvaol concentrations in oregano brands were ranging from 25.57 μg/g ± 0.35- 28.70 μg/g ± 0.36 and 19.07 μg/g ± 0.38 - 48.10 μg/g ± 0.62, respectively. In conclusion, the developed method was capable to identify and determine ursolic acid and uvaol in pure powder and natural matrices with good linearity, accuracy and precision.